The "Gender Factor" in Wearing-Off among Patients with Parkinson's Disease: A Post Hoc Analysis of DEEP Study. (20th January 2015) - Colombo, Delia; Abbruzzese, Giovanni; Antonini, Angelo; Barone, Paolo; Bellia, Gilberto; Franconi, Flavia; Simoni, Lucia; Attar, Mahmood; Zagni, Emanuela; Haggiag, Shalom; Stocchi, Fabrizio
Abstract : Background . The early detection of wearing-off in Parkinson disease (DEEP) observational study demonstrated that women with Parkinson's disease (PD) carry an increased risk (80.1%) for wearing-off (WO). This post hoc analysis of DEEP study evaluates gender differences on WO and associated phenomena. Methods . Patients on dopaminergic treatment for ≥1 year were included in this multicenter observational cross-sectional study. In a single visit, WO was diagnosed based on neurologist assessment as well as the use of the 19-item wearing-off questionnaire (WOQ-19); WO was defined for scores ≥2. Post hoc analyses were conducted to investigate gender difference for demographic and clinical features with respect to WO. Results . Of 617 patients enrolled, 236 were women and 381 were men. Prevalence of WO was higher among women, according to both neurologists' judgment (61.9% versus 53.8%, P = 0.045 ) and the WOQ-19 analysis (72.5% versus 64.0%, P = 0.034 ). In patients with WO (WOQ-19), women experienced ≥1 motor symptom in 72.5% versus 64.0% in men and ≥1 nonmotor symptom in 44.5% versus 36.7%, in men. Conclusions . Our results suggest WO as more common among women, for both motor and nonmotor symptoms. Prospective studies are warranted to investigate this potential gender-effect.